2005
DOI: 10.1590/s1678-77572005000200021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the bleached human enamel by Scanning Electron Microscopy

Abstract: ince bleaching has become a popular procedure, the effect of peroxides on dental hard tissues is of great interest in research. Purpose: The aim of this in vitro study was to perform a qualitative analysis of the human enamel after the application of in-office bleaching agents, using Scanning Electron Microscopy (SEM). Materials and Methods: Twenty intact human third molars extracted for orthodontic reasons were randomly divided into four groups (n=5) treated as follows: G1-storage in artificial saliva (contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
49
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 13 publications
10
49
0
3
Order By: Relevance
“…However, its potential of remineralization is not equivalent to the natural saliva in vivo, and fluoride ions in the oral cavity are essential to the balance of the demineralization process. [12] SEM images showed the dissolution of enamel organic layer (G 2 , G 3 and G 4 ), however, there was no loss of the non-prismatic layer of enamel surface, in discordance with Markovic et al, [13] who reported a dissolution of the nonprismatic layer and exposure of prisms after long exposure to agents with high percentage of hydrogen peroxide. The most severe effect of 38% hydrogen peroxide observed in this experiment resulted from the keeping of the samples in distilled water; [13] the effects of 38% hydrogen peroxide in our samples were probably mitigated by immersion in artificial saliva.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…However, its potential of remineralization is not equivalent to the natural saliva in vivo, and fluoride ions in the oral cavity are essential to the balance of the demineralization process. [12] SEM images showed the dissolution of enamel organic layer (G 2 , G 3 and G 4 ), however, there was no loss of the non-prismatic layer of enamel surface, in discordance with Markovic et al, [13] who reported a dissolution of the nonprismatic layer and exposure of prisms after long exposure to agents with high percentage of hydrogen peroxide. The most severe effect of 38% hydrogen peroxide observed in this experiment resulted from the keeping of the samples in distilled water; [13] the effects of 38% hydrogen peroxide in our samples were probably mitigated by immersion in artificial saliva.…”
Section: Discussionmentioning
confidence: 58%
“…As well as Oltu and Gurgan, [7] Pinto et al, [3] Efeoglu et al, [1] Miranda et al, [12] Faraoni-Romano et al, [10] artificial saliva was used in this study (G 1 ; pH=7.0) to simulate mouth conditions. However, its potential of remineralization is not equivalent to the natural saliva in vivo, and fluoride ions in the oral cavity are essential to the balance of the demineralization process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the potential for remineralization is equivalent to the in vivo natural saliva, and fluoride ions in the oral cavity are essential for the balance in the demineralization-remineralization process. 12 The most severe effect of hydrogen peroxide 38% was due to the storage of specimens in distilled water; the effects of hydrogen peroxide 38% in our specimens were probably softened by immersion in artificial saliva.…”
Section: Discussionmentioning
confidence: 66%
“…A erosão do esmalte seria uma conseqüência ao aumento da porosidade e deposição de precipitado. Depressões com formação de crateras, remoção da camada aprismática e exposição dos prismas de esmalte também podem ser detectados 37 . Ao serem observadas as amostras dos dentes do GIII (controle) podem-se constatar severas alterações que são significativas com grande número de crateras de diferentes profundidades distribuídas em meio a áreas de perda da camada superficial do esmalte.…”
Section: Figura 5 Fotomicrografia Do Dente Do Grupo II Apresentando unclassified